2022
DOI: 10.1371/journal.pone.0266506
|View full text |Cite
|
Sign up to set email alerts
|

Mitonuclear genetic patterns of divergence in the marbled crab, Pachygrapsus marmoratus (Fabricius, 1787) along the Turkish seas

Abstract: Biogeographical transition zones present good opportunities for studying the effect of the past ice ages on genetic structure of species because secondary contact zones of post-glacial lineages can be formed. In this study, we investigated the population genetic structure of the marbled rock crab, Pachygrapsus marmoratus along the coasts of Turkey. We genotyped 334 individuals from the Black Sea, the Turkish Straits System (TSS), the Aegean, and the Eastern Mediterranean basins. In order to reveal its evolutio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 77 publications
(115 reference statements)
0
1
0
Order By: Relevance
“…Previous genetic studies based on microsatellite polymorphisms (Fratini et al, 2008;Silva et al, 2009;Fratini et al, 2011;Fratini et al, 2013;Deli et al, 2016;Iannucci et al, 2020;Çetin et al, 2022) and mtDNA sequencing (Fratini et al, 2011;Kalkan et al, 2013;Deli et al, 2016;Fratini et al, 2016;Çetin et al, 2022) revealed weak but significant genetic heterogeneity among marbled crab populations in different areas including the Atlantic Ocean, the Black Sea and several Mediterranean Sea regions. In addition, former microsatellite studies, based on population samples separated by a few hundred kilometres, indicated that deviation from panmixia might occur at a small geographic scale, albeit the lack of geographically coherent differentiation suggests the existence of genetic patchiness.…”
Section: Introductionmentioning
confidence: 98%
“…Previous genetic studies based on microsatellite polymorphisms (Fratini et al, 2008;Silva et al, 2009;Fratini et al, 2011;Fratini et al, 2013;Deli et al, 2016;Iannucci et al, 2020;Çetin et al, 2022) and mtDNA sequencing (Fratini et al, 2011;Kalkan et al, 2013;Deli et al, 2016;Fratini et al, 2016;Çetin et al, 2022) revealed weak but significant genetic heterogeneity among marbled crab populations in different areas including the Atlantic Ocean, the Black Sea and several Mediterranean Sea regions. In addition, former microsatellite studies, based on population samples separated by a few hundred kilometres, indicated that deviation from panmixia might occur at a small geographic scale, albeit the lack of geographically coherent differentiation suggests the existence of genetic patchiness.…”
Section: Introductionmentioning
confidence: 98%